Menyikapi Perbedaan Pandangan Christology from Above and Christology from Below - Robert Pangaribuan (SOTIRIA (Jurnal Theologia dan Pendidikan Agama Kristen), 2019)
The existence of Jesus in the world at the past time has raised many questions about who He really is. He has the power to carry out powerful and miraculous services that other ordinary human beings cannot possibly do. Pluralists and Liberals question the existence of Jesus; is he really the God who has descended from heaven and become human. To see the existence of the two, it is known the Christology from above and below. This article aims to criticize that theory. The method used is descriptive, using related variables to explain the ratio of both theories of Christology. Abstrak: Kehadiran Yesus di dalam dunia pada masa lalu telah memunculkan banyak pertanyaan tentang siapakah Dia sesungguhnya. Ia berkuasa melakukan pelayanan yang penuh kuasa dan mujizat yang tidak mungkin dapat dilakukan oleh manusia biasa lainnya. Kaum Pluralis dan aliran Liberal mempersoalkan keberadaan Yesus; apakah Ia benar-benar Tuhan yang telah pernah turun dari surga dan menjadi manusia. Untuk melihat keberadaan yang dua itu dikenallah teori Kristologi atas dan bawah. Artikel ini bertujuan untuk mengkritisi teori tersebut. Metode yang digunakan adalah deskriptif, menggunakan iteratur yang terkait untuk menjelaskan nisbah kedua teori kristologi tersebut.